Geological structure, recharge processes and underground drainage of a glacierised karst aquifer system, Tsanfleuron-Sanetsch, Swiss Alps - Gremaud, Vivian; Goldscheider, Nicola; Savoy, Ludovic; Favre, Gérald; Masson, Henri (My University, 2009)
The relationships between stratigraphic and tectonic setting, recharge processes and underground drainage of the glacierised karst aquifer system ‘Tsanfleuron-Sanetsch’ in the Swiss Alps have been studied by means of various methods, particularly tracer tests (19 injections). The area belongs to the Helvetic nappes and consists of Jurassic to Palaeogene sedimentary rocks. Strata are folded and form a regional anticlinorium. Cretaceous Urgonian limestone constitutes the main karst aquifer, overlain by a retreating glacier in its upper part. Polished limestone surfaces are exposed between the glacier front and the end moraine of 1855/1860 (Little Ice Age); typical alpine karrenfields can be observed further below. Results show that (1) large parts of the area are drained by the Glarey spring, which is used as a drinking water source, while marginal parts belong to the catchments of other springs; (2) groundwater flow towards the Glarey spring occurs in the main aquifer, parallel to stratification, while flow towards another spring crosses the entire stratigraphic sequence, consisting of about 800 m of marl and limestone, along deep faults that were probably enlarged by mass movements; (3) the variability of glacial meltwater production influences the shape of the tracer breakthrough curves and, consequently, flow and transport in the aquifer.
Keywords: Karst; Retreating glacier; Multi-tracer test; Climate change; Switzerland